SOCIAL SUMMARY OF THE SOCIETY OF THE BUKHARA EMIRATE AT THE END OF THE 19TH - BEGINNING OF THE 20TH CENTURIES - Kuvvatova N. (American Journals Publishing, 2024)
This article examines the social structure of the Bukhara Emirate in the second half of the XIX - early XX centuries, traces the dynamics of changes that have occurred in the social stratification of the state against the background of a change in the political status of the emirate as a result of the establishment of a protectorate of the Russian Empire. The article also analyzes the qualitative composition of the layers and groups of the population of the Bukhara Emirate, and also contains information about their numerical composition.
Keywords: Emiratee, population, social structure, class division, layer, group, settled population, nomadic population, numerical composition, clergy.